Improving early childhood teachers' competence through deep learning model mentoring to shape Pancasila student profiles in East Java - Dwi Astutiek; Dwi Retnani Srinarwati; A.V. Sri Suhardiningsih; Anies Listyowati; Mohammad Falah Alfitamma (Community Empowerment, 2026)
The implementation of the Merdeka Curriculum requires a paradigm shift from surface learning to deep learning. This community service program aims to enhance Early Childhood Education (ECE) teachers' pedagogical competence in designing Deep Learning-based instruction aligned with the Pancasila Student Profile. Utilizing a participatory approach, the program included pedagogical training, coaching clinics, and reflective classroom mentoring. Program effectiveness was measured through self-efficacy pre-tests and post-tests, classroom observations, and lesson plan analysis. Results indicated a significant increase in teacher self-efficacy, with mean scores rising from 3.01 to 3.96 (a 31.5% increase; p < 0.01). The highest specific gains were recorded in the ability to use inquiry-based open questions (41.0%) and critical project design (38.6%). Qualitatively, a transformation in teaching practices was observed, characterized by the use of relevant local contexts, explicit communication of learning goals, and consistent scaffolding of critical reasoning. These findings confirm that reflective practice-based mentoring effectively drives a measurable and sustainable transition toward deep learning pedagogy in ECE settings.